Jagged blue frontiers: The police and the policing of boundaries in South Africa - Lamb, Guy (2017)
Social and territorial boundaries have been fundamental to the approaches and practices of policing bodies in South Africa for centuries, from the mounted colonial paramilitary forces of the 1800s to the 21st century professional police. Boundaries have not only been a central mechanism that the police have consistently used to control and regulate the general population, but have also been catalysts for change in terms of operational policing strategies and tactics. This has typically been the case when a threat has been ascribed to a bounded area and/or populations that reside within the confines of the boundary, or on the other side of the boundary. The nature of the such a threat is considered to be even more severe when communities within the bounded space, or on the other side of the boundary, acquire significant quantities of firearms and ammunition, as this provides such populations with the lethal technology to defy and contest the police's coercive authority and ability to conserve boundaries relating to the maintenance of order and the enforcement of laws. South Africa is a distinctly relevant case study for an examination of the relationship between boundaries and the police as for the past three and a half centuries South Africa's diverse policing history has been profoundly framed by territorial, social and political boundaries. The police and the proto-police have been at the sharp edge of the application of authority by assorted forms of government, and have often acted to safeguard the interests of economic and political elites. That is, the police and formal policing bodies have been required to subdue and suppress groups and individuals that resisted or threatened the process of state building and resource extraction. The police were also regularly deployed to protect the territorial borders of South Africa from menacing others. By means of this historical analysis of South Africa, this thesis introduces a new concept, 'police frontierism', which illuminates the nature of the relationships between the police, policing and boundaries, and can potentially be used for future case study research. It is an alternative way of conceptualising policing, one in which police work is fundamentally framed by social and territorial boundaries. Such boundaries delineate perceived safe or 'civilised' spaces from dangerous or 'uncivilised' ones. The police tend to concentrate their resources in the frontier zone immediately adjacent to the boundary in order to preserve or extend the boundary of safety and 'civilisation', and restrict, subdue or eliminate those individuals, groups or circumstances from the 'uncivilised' spaces that a government authority or elites have deemed to be a threat to order and peace. An essential dynamic of this policing approach is that the boundary and the adjoining frontier zone strongly influence police practices and behaviour in this context. In particular, territorial and social delineations amplify and distort existing police prejudices against those communities on the other side of the boundary. The police often engage in othering, where the communities of interest are viewed negatively, and are predominantly seen as agents of disorder and law breaking. This othering may lead to an intensification of aggressive police behaviour towards the targeted communities